Comparative Study of Vegetable Biodiversity in Terai and Hilly Belts of Chitwan, Nepal - Devkota, Pukar; Mishra, Sharoj R. (Nepal Journal of Science and Technology, 2020)
The study was conducted to assess biodiversity and conservation aspects of vegetable crops in two different geographical areas of the Chitwan district. The household survey was carried out in Kailash (hill) and Nayabasti (terai) of Chitwan. Descriptive analysis, mean comparison, correlations, and biodiversity indices were used for data analysis. On the basis of biodiversity index, evenness, the adequate number of species, and Sorenson’s coefficient, open-pollinated (OP) (nonhybrid) vegetables were more diverse in hills than in terai, while hybrid vegetables are more diverse in terai than in hills. Hybrid vegetables were mostly grown in terai, where the use of chemical fertilizers and pesticides was also higher. OP vegetables dominated hilly areas. Gurung ethnic community had a significant role in the conservation of indigenous vegetable biodiversity. The primary source of seed was home storage in the case of OP vegetables in hills. However, in terai, agro-concerns were used as a significant source of seeds, followed by co-operatives. Co-operatives’ involvement was high in terai as compared to hills, but the role was not significant in vegetable farming. In contrast, assistance in vegetable farming from agriculture service provider organizations was higher in hills as compared to terai. The major problem in vegetable farming was lack of irrigation in both areas, followed by market inaccessibility in hills, whereas climate change was rising as a problem in terai. Markets of produced goods were farm gate, local markets, and distant markets. A middleman mostly did the price determination of the products. Off-season vegetable farming was not practiced in the study areas. However, off-farm vegetable production was typical in hilly areas. Indigenous and OP vegetable biodiversity has been facing various challenges despite their roles in nutrition, indigenous knowledge promotion, and food security. Hence, it is suggested to strengthen government policy toward irrigation facility development, gene bank establishment, marketing facilities, and technology transfer and develop on-farm community based intense organizations for sustainable vegetable diversity conservation.